Analisis Asam Valproat dalam Plasma Secara Kromatografi Gas - Susanti, Ani; Harahap, Yahdiana; Harmita, Harmita (Majalah Ilmu Kefarmasian, 2010)
Valproic acid is an anticonvulsant drug that works by increasing the levels of γ-aminobutyric acid (GABA). Determination of valproic acid is quite difficult because it has no chromophore groups in its structure. Aa analytical method using gas chromatography (GC) with flame ionization detector for the determination of valproic acid in human plasma has been developed and optimized. Valproic acid was extracted from plasma by liquid-liquid extraction method using diethyl ether. The optimum analysis conditions for valproic acid in plasma were achieved by regulated gas chromatography injector and detector at a temperature of 250oC and temperature programming with an initial temperature of 70oC and 5oC temperature increasing per minute until a temperature of 100oC, then held for 1 minute. Then the temperature was increased by 2°C per minute until the column temperature to 150oC. The optimum conditions of analysis took 32 minutes. In the concentration range from 40.0 to 100.0 µg/mL yielded a linear calibration curve with correlation coefficient (r) of 0.9894. Accuracy (% diff) of this method was -13.67% to 12.33% with precision (CV) between 9.33% to 14.92%, and relative recovery test was 86.33% to 112.33%.